Kampanye Pilpres 2014 dalam Konstruksi Akun Twitter Pendukung Capres - Firmansyah, Mas Agus; Karlinah, Siti; Sumartias, Suwandi (Universitas Semarang, 2017)
The use of social media, especially Twitter during the presidential election campaign in 2014 led to the construction of the presidential candidates can not only be found in the mass media, but also can be found in the content chirp twitter account supporters. This study aims to identify and find out how the two presidential candidates figure (Prabowoand Jokowi) when constructed through chirp Twitter account their respective supporters. By using qualitative methods, this research observation and analysis of the chirp twitter supporters of the two presidential candidates were uploaded during the presidential election campaign (June 4 until June 5, 2014) takes place. The results showed that Prabowo is constructed by supporters twitter account as a highly intelligent, resolute and strong. While Jokowi constructed by supporters as a populist figure, simple and honest.